Framework to Automate the Reimbursement in the Courier Service in Peru based on Blockchain - Hinostroza-Dueñas, Enzo (2024)
Courier services face substantial customer satisfaction and operational efficiency challenges, exacerbated by traditional processes marred by lack of transparency, delays and the need for intermediary interventions. The need to efficiently manage refunds in situations such as loss, damage or delay is essential to maintain customer satisfaction and service integrity. Therefore, the present study proposes a framework to automate reimbursement in Courier services in Peru by applying Blockchain technology. The proposed framework is composed of 3 phases: (1) Elaboration of the Blockchain technology structure, (2) Creation of smart contracts and (3) Design of web applications. Blockchain technology is used to ensure decentralization and automation. The proposed framework was validated by 2 experts and 10 users by applying 2 experiments and a survey based on expert opinion. The results indicate that with the proposed framework an outstanding reduction in both processing time and number of errors is achieved in the delineated scenarios, where a significant decrease of 99.97% in the time needed to manage refunds stands out. In addition, the survey results show that the "Objective of the solution", the "Technical tools" and the "Application" of the system have an average value of 4.7 (Value close to 5).